THE EFFECT OF INFLATION, INTEREST RATE AND EXCHANGE RATE ON INDONESIA'S BALANCE OF PAYMENTS - Nyimas Adheana Darnita; Weri; Asri Diana; Fitriyani; Diana Sapha A.H (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyse the effect of inflation, interest rate and exchange rate on Indonesia's balance of payments by using annual data for the period 1993-2024. The method used is Autoregressive Distributed Lag (ARDL) which is able to identify short-term and long-term effects simultaneously, and accommodate the characteristics of non-stationary time series data with different levels of integration. The results show that in the short term, inflation has a positive effect, while exchange rates and interest rates have a negative effect on the balance of payments. Meanwhile, in the long run, exchange rates and interest rates have a positive effect, and inflation has a negative but insignificant effect. The novelty of this study lies in the use of ARDL model with long data coverage and explicit separation between short-run and long-run dynamics, which has rarely been comprehensively discussed in previous studies related to the balance of payments in Indonesia. The government's role is required to maintain price and interest rate stability through adaptive exchange rate management in order to maintain Indonesia's balance of payments.